Descriptive analysis of analogies between information security management and queuing systems - Мохор, Володимир Володимирович; Бакалинский, Александр Олегович; Богданов, Александр Михайлович; Цуркан, Василий Васильевич (Ukrainian Information Security Research Journal, 2017)
It is established that none of the existing international standards contains specific methods for the development of project requirements for the information security management system applied to a particular organization for now. To overcome this limitation it is considered a possible analogy of queuing systems and information security management systems. A descriptive analysis of possible analogies is carried out by comparing the composition and the general functional model of the queuing system. On the basis of this comparison, it is established that the mathematical apparatus of the theory of queuing systems can be used to formulate project requirements for the information security management system. This will allow the development of the model of such system. It will be possible to determine sensitivity of different aspects of information security applied to a particular organization with its help.